Kontrol Diri dan Kepribadian Narsistik Pengguna Media Sosial Instagram pada Generasi Milenial - Meralda, Monica Tasya Olivia; Soetjiningsih, Christiana Hari (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
This study aims to determine the relationship between self-control and the narcissistic personality of Instagram social media users in the millennial generation. This study used a correlational quantitative method. Participants in this study were all millennials aged 23-42 years, both men and women, who used electronic devices in the form of gadgets, laptops, and computers, had Instagram social media accounts, and were users for more than six months. Sampling in this study used a convenience sampling technique with a total sample of 205 respondents. The measuring instruments used in this study were the Self-Control Scale from Tangney, Baumeister, and Boone (2004) to measure self-control variables and the Narcissistic Personality Inventory (NPI) Scale from Raskin and Terry (1988) to measure narcissistic personality variables. The results of data analysis using the Pearson product-moment correlation technique were obtained with a correlation number of -0.190 with a significance value of 0.003 (p<005). The results of this study show that self-control has a significant negative relationship with the narcissistic personality of Instagram social media users in the millennial generation, which means that the higher the self-control, the lower the narcissistic tendency. Conversely, the lower the self-control, the higher the narcissistic tendency.